2021
DOI: 10.3389/fcvm.2021.639727
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 Functions in Atherosclerosis Are Not Limited to Plasmatic LDL-Cholesterol Regulation

Abstract: The relevance of PCSK9 in atherosclerosis progression is demonstrated by the benefits observed in patients that have followed PCSK9-targeted therapies. The impact of these therapies is attributed to the plasma lipid-lowering effect induced when LDLR hepatic expression levels are recovered after the suppression of soluble PCSK9. Different studies show that PCSK9 is involved in other mechanisms that take place at different stages during atherosclerosis development. Indeed, PCSK9 regulates the expression of key r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 128 publications
0
39
0
Order By: Relevance
“…Several studies have demonstrated that SMCs secrete functional PCSK9 into the atheroma that exerts effects on monocytes migration in the intima. The overexpression of PCSK9 by SMCs in atherosclerotic plaques also reduces the ability of macrophages to ingest aggregated LDL (agLDL) and oxLDL molecules through scavenger receptors and LDLR related proteins [4,65]. PCSK9 secreted by SMCs not just plays a paracrine effect, PCSK9 also regulates the metabolism in SMCs.…”
Section: Inflammation and Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that SMCs secrete functional PCSK9 into the atheroma that exerts effects on monocytes migration in the intima. The overexpression of PCSK9 by SMCs in atherosclerotic plaques also reduces the ability of macrophages to ingest aggregated LDL (agLDL) and oxLDL molecules through scavenger receptors and LDLR related proteins [4,65]. PCSK9 secreted by SMCs not just plays a paracrine effect, PCSK9 also regulates the metabolism in SMCs.…”
Section: Inflammation and Atherosclerosismentioning
confidence: 99%
“…Hepatocytes are the primary source of PCSK9 that is secreted into the circulation. However, also other cells can produce and secrete PCSK9, like cells in the intestines [3,4], pancreas [5], adipose tissue [6], kidneys [7] and brain [8]. Interestingly, the circulating levels of PCSK9 biologically increases in the late night, and decreases in the late afternoon, following a diurnal rhythm [9].…”
Section: Introductionmentioning
confidence: 99%
“…Many large clinical trials have revealed that PCSK9 inhibitors can decrease LDL-C level significantly and ameliorate the main adverse cardiovascular events and even reverse plaque accumulation (13,32,33). Recent studies have provided more evidence of the PCSK9 on macrophages by promoting cholesterol uptake, inhibiting cholesterol efflux, and activating inflammation or apoptosis (15,34). We have found (10) that Hcy promoted lipid accumulation mainly by regulating receptors responsible for cholesterol efflux.…”
Section: Discussionmentioning
confidence: 75%
“…In recent years, PCSK9 has attracted much attention in the field of lipid-lowering because of the powerful reduction of plasma LDL-C levels, amelioration of main adverse cardiovascular events and effect on stabilizing plaques with its inhibition (12,13). In addition to promoting the lysosomal degradation of LDL receptor LDLR on the surface of hepatocytes (14), PCSK9 can also act directly on blood vessel walls, by disrupting lipid intake and efflux of macrophages, promoting the secretion of inflammatory factors and inducing apoptosis to participate in atherosclerosis and even plaque destabilization (15,16). Ding et al (17) found that silencing PCSK9 in THP-1 macrophages could inhibit the formation of foam cells by downregulating the scavenger receptor CD36.…”
Section: Introductionmentioning
confidence: 99%
“…Further data suggest that the nuclear factor kappa B (NF-κB) signaling pathway plays a key role in PCSK9-mediated vascular inflammation and thrombosis [27][28][29]. In fact, PCSK9 inhibition by using small interfering RNA (siRNA) has shown to suppress expression of LOX-1 and secretion of pro-inflammatory cytokines in macrophages by inhibiting NF-κB translocation into the nucleus [29][30][31][32][33].…”
Section: Pcsk9 and Inflammation/thrombosismentioning
confidence: 99%